Workplace anxiety leading to job burnout among young and middle-aged university lecturers: mechanism and mitigation strategies - Zhou, Kun; Wang, Jin (Frontiers in Psychology, 2025)
A growing group of young and middle-aged lecturers in universities, during a time of increasing career aspirations, not only bears the significant responsibility of teaching but also serves as the backbone for promoting the high-quality development of higher education in our country. Simultaneously, they are experiencing varying degrees of workplace anxiety.Methods ： This paper adopts the mixed-methods of questionnaire analysis and semi-structured interview. Firstly, it presents a questionnaire designed to assess perceptions of workplace anxiety, job performance, and job burnout. Secondly, data were collected from 506 young and middle-aged lecturers across 10 colleges and universities in the four provinces of Chongqing, Anhui, Beijing, and Hebei in China through online questionnaires. A total of 449 valid questionnaires and 56 interview transcripts were obtained. Subsequently, SPSSAU online data analysis software was employed to test the hypotheses derived from the questionnaire data using confirmatory factor analysis, correlation analysis, and Bootstrap sampling analysis.Additionally, qualitative analysis was conducted in conjunction with the interview transcripts.The results indicate that, on one hand, there is a significant positive relationship between the perception of workplace anxiety and the career growth expectations of young and middle-aged university lecturers. This is evidenced by a negative correlation with their perception of job performance and a positive correlation with their perception of competitive pressure. On the other hand, self-efficacy plays a moderating role in alleviating workplace anxiety and burnout among young and middle-aged university lecturers. As their sense of self-efficacy increases, their feelings of workplace anxiety diminish.The increasing competition among peers has posed significant challenges to the physical and mental health of young and middle-aged university lecturers.Reforming competitive mechanisms and establishing a career support system are essential, evidence-based strategies for alleviating workplace anxiety and enhancing professional efficacy.This article explores the relationship between workplace anxiety and job burnout among young and middle-aged university lecturers, while also proposing strategies for mitigation. These insights are crucial for promoting the career development of university lecturers and safeguarding their physical and mental well-being.